Territorial planning and socio-environmental conflicts related to mining: Huasco and Chubut provinces in defense of the territory - Mora Castillo, María Alejandra; Alvarez Manriquez, Lorena Vanesa (Universidad Pedagógica y Tecnológica de Colombia, 2021)
In recent decades, there has been an increase in socio-environmental conflicts around mining in Latin America as a result of the impact of the extractivist model on local communities. As a result, different repertoires of collective action have been generated around these conflicts, whose origin is not only the product of macroeconomic policies, but also are protected by territorial and environmental institutions that favor the intervention of external economic actors. The objective of this article is to analyze the implications of land management policies in the processes of socio-environmental conflict, based on the study of two mining conflicts, one in the province of Huasco, Chile, and the other in the province of Chubut, Argentina. The methodology introduced a recognition of the characteristics of the territories that was complemented with a documentary search on the development of the conflict, the actors and the environmental and territorial regulations in force in both countries. The results presented are partial and were developed within the framework of a larger research work. As a conclusion, it is proposed that territorial planning is not only a planning instrument, but also a process to articulate interests and territorialities, generally opposed, that the more they consider a participatory logic of the different actors that occupy the territory, the more sense it will have for those who live there.